Prion‐like Aggregation of Mitochondrial Antiviral Signaling Protein in Lupus Patients Is Associated With Increased Levels of Type I Interferon. Issue 11 (27th October 2016) - Shao, Wen‐Hai; Shu, Daniel H.; Zhen, Yuxuan; Hilliard, Brendan; Priest, Stephen O.; Cesaroni, Matteo; Ting, Jenny P.‐Y.; Cohen, Philip L.
Abstract : Objective: Increased levels of type I interferon (IFN) and type I IFN–regulated genes are found in patients with systemic lupus erythematosus (SLE) and may be central to its pathogenesis. Mitochondrial antiviral signaling protein (MAVS) is a key regulator of type I IFN that undergoes a dramatic prion‐like aggregation and self propagates the activation signal from viral RNA to amplify downstream IFN production. We undertook this study to determine whether such MAVS aggregates might play a role in the sustained increased production of type I IFN in SLE. Methods: Peripheral blood mononuclear cells were isolated and mitochondrial extracts were prepared. MAVS aggregation was detected by semidenatured agarose gel electrophoresis and confirmed by immunofluorescence staining. MAVS‐associated signaling proteins were analyzed by Western blotting. MAVS aggregation–associated gene expression signature was analyzed by microarray. Results: In blood cells from 22 of 67 SLE patients, essentially all MAVS was in a high molecular weight aggregated form. None of 6 rheumatoid arthritis patients and only 3 of 33 healthy controls had abnormal MAVS. Compared to MAVS aggregate–negative patients, MAVS aggregate–positive SLE patients had significantly higher serum levels of IFNβ and significantly increased levels of autoantibodies against Sm and U1 RNP. Gene array data revealed a characteristic gene expression pattern in these patients, with altered expression of genes involved in IFN signaling and membrane trafficking. Conclusion: Persistent MAVS aggregates may lead to increased type I IFN production and result in unmitigated signals leading to autoimmunity.